Drug-resistant microorganisms with a higher fitness – can medicines boost pathogens?. (November 2013) - Vanaerschot, Manu; Decuypere, Saskia; Berg, Maya; Roy, Syamal; Dujardin, Jean-Claude
<x xml:space="preserve">Abstract</x> Drug-resistant microorganisms (DRMs) are generally thought to suffer from a fitness cost associated with their drug-resistant trait, inflicting them a disadvantage when the drug pressure reduces. However, Leishmania resistant to pentavalent antimonies shows traits of a higher fitness compared to its sensitive counterparts. This is likely due the combination of an intracellular pathogen and a drug that targets the parasite's general defense mechanisms while at the same time stimulating the host's immune system, resulting in a DRM that is better adapted to withstand the host's immune response. This review aims to highlight how this fitter DRM has emerged and how it might affect the control of leishmaniasis. However, this unprecedented example of fitter antimony-resistant Leishmania donovani is also of significance for the control of other microorganisms, warranting more caution when applying or designing drugs that attack their general defense mechanisms or interact with the host's immune system.